Planning Cemeteries: Their Potential Contribution to Green Infrastructure and Ecosystem Services - McClymont, Katie; Sinnett, Danielle (Frontiers in Sustainable Cities, 2021)
Cemeteries are often included in typologies of green infrastructure features, but there has been little exploration of their role within a multifunctional network of green infrastructure. This paper uses national greenspace data to map the contribution that cemetery space makes to accessible greenspace England. In doing so we provide a more comprehensive and detailed analysis of the scale of cemetery space in contemporary settlements, finding that cemeteries provide around 4% of accessible greenspace and are particularly important in high-density urban environments. Focusing then on an in-depth analysis of an urban case study, we survey 11 cemeteries that provide accessible greenspace for neighbourhoods in Bristol, UK. This suggests that cemeteries are delivering, or have the potential, to deliver ecosystem services and therefore form an important component of green infrastructure networks, but at the same time also need to provide culturally sensitive space for burial and remembrance. Despite the rhetoric, planning policy for cemeteries is not consistent in articulating their role as green infrastructure. We highlight the opportunities for greater cultural, regulation and maintenance services to be delivered, but also the need for greater dialogue between the different players involved in the maintenance and delivery of cemeteries.